2018
DOI: 10.28959/jdpi.v29i2.3745
|View full text |Cite
|
Sign up to set email alerts
|

PROSES PENGINSTANAN AGLOMERASI KERING DAN PENGARUHNYA TERHADAP SIFAT FISIKO KIMIA KOPI BUBUK ROBUSTA (Coffea robusta Lindl. Ex De Will)

Abstract: Penelitian ini bertujuan untuk memperoleh data dan informasi tentang paket teknologi pengolahan produk kopi berbahan baku robusta dengan cepatnya waktu kristalisasi terkait dengan karakteristik kopi instan yang dihasilkan termasuk penurunan kadar kafein. Penggunaan kopi robusta sebagai bahan baku dalam proses pembuatan kopi instan merupakan salah satu alternatif dalam melakukan proses hilirisisasi kopi terutama bagi industri kecil dan menengah dengan kualitas yang cukup baik. Di samping itu karena kopi robusta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…It showed that antioxidant activity increase along addition of turmeric and lower temperature. It was found that the greater the addition of turmeric extract to the cookie dough, the higher the antioxidant activity contained in cookies [10]. In the composition of cookies with the addition of 20% white turmeric extract, it is known that the antioxidant activity of DPPH contained is 54%, 59% with the addition of 40% white turmeric extract, and 64% with the addition of 60% white turmeric extract.…”
Section: Changes In Antioxidant Activitymentioning
confidence: 99%
“…It showed that antioxidant activity increase along addition of turmeric and lower temperature. It was found that the greater the addition of turmeric extract to the cookie dough, the higher the antioxidant activity contained in cookies [10]. In the composition of cookies with the addition of 20% white turmeric extract, it is known that the antioxidant activity of DPPH contained is 54%, 59% with the addition of 40% white turmeric extract, and 64% with the addition of 60% white turmeric extract.…”
Section: Changes In Antioxidant Activitymentioning
confidence: 99%
“…24, No.2, September 2020, ISSN 1410-1920, EISSN 2579 Ruri Wijayanti dan MalseAnggia ================================================================================ basah (wet basis) atau berdasarkan berat kering (dry basis). Kadar air pada kopi sangat berpengaruh pada pertumbuhan mikroorganisme, khususnya jamur, tetapi kadar air hasil penelitian ini masih jauh lebih kecil dari kondisi optimum untuk pertumbuhan jamur okratoksin (Gafar, 2018).…”
Section: Pelaksanaan Penelitianunclassified
“…Coffee amps contain 12.4% cellulose, 39.1% hemicellulose, and 23.9% lignocellulose, nitrogen: 2.1-2.79, C/N ratio: 16.91, fat: 2.29, protein: 17.44. [10,11,12].…”
Section: Introductionmentioning
confidence: 99%